Synthesis and Characterization of Cellulose Acetate Derived from Corn Stalk Cellulose Using FTIR Analysis - Farisah Masturoh; Nur Hasanah; Kindriari Nurma Wahyusi (G-Tech: Jurnal Teknologi Terapan, 2025)
The synthesis and characterization of cellulose acetate were carried out using cellulose derived from corn stalks. Cellulose acetate was obtained through the esterification of cellulose, a natural biopolymer commonly sourced from wood or plant fibers. During the acetylation stage, the hydroxyl groups in cellulose were replaced with acetate groups from acetic anhydride. The acetylation process involved varying the volume of glacial acetic acid (CH₃COOH) at 25, 35, 45, 55, and 65 milliliters and reaction times of 1, 1.25, 1.5, 1.75, and 2 hours, using 0.5 milliliters of 98 percent sulfuric acid as a catalyst. Cellulose was first extracted by delignification using 17.5 percent sodium hydroxide, followed by bleaching with 4 percent sodium hydroxide and 4 percent hydrogen peroxide. The results showed that increasing the volume of acetic acid led to an acetyl content of up to 40.4 percent and a degree of substitution of 2.5. Extension of the acetylation time to 1.5 hours also increased the yield of cellulose acetate to a maximum of 70.2631 percent before decreasing at longer durations. These optimal results, including 70.2631 percent yield, 40.4 percent acetyl content, and a degree of substitution of 2.5, were achieved with 65 milliliters of acetic acid and 1.5 hours of acetylation. FTIR analysis confirmed successful acetylation by identifying hydroxyl (O–H), carbonyl (C=O), and ester (C–O) functional groups.